Penilaian Perumahan Berdasarkan Kriteria Rumah Sehat Menggunakan Metode Fuzzy Multicriteria Decision Making - Muhammad Hadi Saputra; Azrai Sirait ((JurTI) Jurnal Teknologi Informasi, 2018)
Abstract - A healthy home is very important for human life. The advantage can avoid various environmental-based diseases such as ARI, which affects many infants, tuberculus, diarrhea and avoid vector-borne diseases such as dengue fever, malaria, PES and Filariasis. In addition to avoiding a variety of healthy home ailments can affect healthy behavior in humans that affect the quality of human resources. Therefore it is necessary to hold regular assessments to assess housing based on the criteria of a healthy home so that all desires are expected to be achieved properly. The use of the method in this housing case is Fuzzy Multi Criteria Decision Making (FMCDM), which this method will provide a decision for the problem at hand. This method helps make decisions in situations where there are many alternative criteria. Keywords - Decision Support Systems, Fuzzy Multi Criteria Decision Making, Healthy Houses